Self-reported perceived stress, depression, and generalized anxiety disorder among Kathak dancers and physically active non-dancers of North India - Kulshreshtha, Monika; Saraswathy, Kallur Nava; Babu, Nandita; Chandel, Shivani (Frontiers in Psychology, 2023)
The aim of the present paper was to study the various common mental disorders in a sample of Kathak dancers and non-dancers of North India. 206 female Kathak dancers and 235 healthy controls, aged 18-45 years completed questionnaires assessing perceived stress (PSS-10), depressive symptoms (PHQ-9), and generalized anxiety (GAD-7). Pearson correlations assessed the association between perceived stress, depression, generalized anxiety, age, and years of dancing, and binary logistic regression identified the risk of developing depression and generalized anxiety disorder in Kathak dancers and non-dancers. The prevalence of perceived stress was similar among Kathak dancers and non-dancers. Kathak dancers reported significantly lower depressive symptoms compared to controls. Non-dancers with elevated perceived stress levels were 4 times more likely to report depressive symptoms and 7 times more likely to report anxiety symptoms, relative to dancers. The adjusted odds of reporting depressive symptoms along with generalized anxiety were higher among non-dancers compared to dancers. Kathak can be developed into a very effective psychotherapeutic tool for mitigating the risk of developing depression and generalized anxiety disorder.